Music(s) of the world as an online EFL resource: A Japanese EFL classroom experience - Rockell, Kim (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This research considers how the study of musical performances from around the world can be drawn upon as a useful resource for language instruction, particularly in EFL Japanese university classrooms. This study shares the insights gained from literature reviews combined with the researcher’s teaching experiences on the advanced English elective course of “Computer-Assisted Ethnomusicology.” This work was carried out over a five-year period between 2013 - 2018 at a university in the Tohoku region of Japan, based on a course that focused on the music and culture found in Oceania, South East Asia, East Asia, Africa, and North America. This study identifies the language resources present within the ethnomusicological content, and identifies the ways it can help awaken learners to the rich variation that exists among the cultures of the world, and highlighting the way local and global features combine in the ‘glocal’. In addition to digital applications, approaches introduced in the study also include the combination of high and low contact activities based on ethnomusicological resources. This helps to emphasize how Massive Open Online Courses (MOOCs), and open-source multimedia make it possible to approach musical song texts and discourses that surround musical practice and performance and apply these to EFL teaching.